2000
DOI: 10.1177/229255030000800201
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Breast Implant Survival Properties and the Management of the Woman with Silicone Gel Breast Implants

Abstract: The survival properties of silicone gel breast implants are dependent on their vintage (year of manufacture), duration in situ and manufacturer. A total of 527 gel implants have been explanted and analyzed in the author's laboratories. Of the 28 first-generation implants (1963 to 1972), 27 (96.4%) remained intact after 14 to 28 years in situ (mean 20.8 years). Of the 216 second-generation implants (1973 to mid-1980s) that were explanted from 1992 to 1998, 158 (73%) had disrupted. Kaplan-Meier survival curves d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 72 publications
0
9
1
Order By: Relevance
“…All 62 implants in this group proved to be intact after a mean time of 8.1 to 9.4 years (range two to 15 years) in situ. By contrast, previous studies have shown that, after a similar time in situ, 20% to 50% of second-generation implants had already ruptured (3,7,10).…”
Section: Discussioncontrasting
confidence: 59%
See 4 more Smart Citations
“…All 62 implants in this group proved to be intact after a mean time of 8.1 to 9.4 years (range two to 15 years) in situ. By contrast, previous studies have shown that, after a similar time in situ, 20% to 50% of second-generation implants had already ruptured (3,7,10).…”
Section: Discussioncontrasting
confidence: 59%
“…In the present study, this reason was given by only 22% of patients, and most of these women presented during the early years of the study (1992 to 1996). The main reason for these differences is likely that many reports have been published, particularly during the past few years, indicating that there is no causal relationship between silicone gel breast implants and medical disease (10,11).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations